2016
DOI: 10.1128/aac.00260-16
|View full text |Cite
|
Sign up to set email alerts
|

RpoN Modulates Carbapenem Tolerance in Pseudomonas aeruginosa through Pseudomonas Quinolone Signal and PqsE

Abstract: bThe ability of Pseudomonas aeruginosa to rapidly modulate its response to antibiotic stress and persist in the presence of antibiotics is closely associated with the process of cell-to-cell signaling. The alternative sigma factor RpoN ( 54 ) is involved in the regulation of quorum sensing (QS) and plays an important role in the survival of stationary-phase cells in the presence of carbapenems. Here, we demonstrate that a ⌬rpoN mutant grown in nutrient-rich medium has increased expression of pqsA, pqsH, and pq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 73 publications
3
19
0
Order By: Relevance
“…It has also been suggested that the Sec pathway could be involved in the translocation of components of multidrug efflux pumps across the bacterial membranes ( Yoneyama et al, 2010 ; Akiba et al, 2013 ; Chaudhary et al, 2015 ), but it is unclear how changes in this translocation could increase resistance in the selected mutants. Tigecycline increased resistance may also come about through modifications of the σ 54 RpoN factor that has been found to modulate P. aeruginosa virulence ( Kazmierczak et al, 2005 ), bacterial tolerance to carbapenems ( Viducic et al, 2016 ), susceptibility to quinolones ( Viducic et al, 2007 ) and survival in the presence of tobramycin ( Viducic et al, 2017 ). Both the Sec pathway and RpoN have been proposed as excellent targets in the search of novel antibiotics ( Jin et al, 2016 ; Lloyd et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that the Sec pathway could be involved in the translocation of components of multidrug efflux pumps across the bacterial membranes ( Yoneyama et al, 2010 ; Akiba et al, 2013 ; Chaudhary et al, 2015 ), but it is unclear how changes in this translocation could increase resistance in the selected mutants. Tigecycline increased resistance may also come about through modifications of the σ 54 RpoN factor that has been found to modulate P. aeruginosa virulence ( Kazmierczak et al, 2005 ), bacterial tolerance to carbapenems ( Viducic et al, 2016 ), susceptibility to quinolones ( Viducic et al, 2007 ) and survival in the presence of tobramycin ( Viducic et al, 2017 ). Both the Sec pathway and RpoN have been proposed as excellent targets in the search of novel antibiotics ( Jin et al, 2016 ; Lloyd et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The results in Supplementary Figure S4 A showed that T1lg65 and T1lg88 respectively exhibit the strongest and the weakest QS-dependent colorization of A136, and T1lg24 has colorization comparable to that of T1lg65. Subsequently, two important regulator genes, luxO and rpoN, respectively considered as positive and negative regulator genes in Vibrio and Pseudomonas [ 28 , 29 , 30 , 31 , 32 ], were chosen for analysis of relative expression level in these three Pseudoalteromonas isolates. Supplementary Figure S4B and Supplementary Figure S4C showed that the relative expression of both luxO and rpoN in three isolates is obviously different.…”
Section: Resultsmentioning
confidence: 99%
“…Because previous reports have shown various roles for PQS, namely as a stress response, for planktonic P. aeruginosa cells exposed to antimicrobials (22,26,(38)(39)(40), we were interested to explore how AQs mediate P. aeruginosa behavior in motile, prebiofilm swarm communities. Additionally, the CRM chemical profile of P. aeruginosa swarms provided evidence that tobramycin exposure cues aspects of PQS production or regulation that carbenicillin does not (Fig.…”
Section: Pqs Promotes Cell Death and Reduced Swarming For Cells Exposmentioning
confidence: 99%